The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3892/etm.2020.8475
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autophagy protects human dental pulp cells from lipopolysaccharide‑induced pyroptotic cell death

Abstract: The NOD-like receptor protein 3/caspase-1 inflammasome can be activated in human dental pulp tissue and fibroblasts; however, the underlying mechanisms are poorly understood. In the present study, lipopolysaccharide (LPS) was used to treat dental pulp cells to establish an inflammation model. Cell viability was examined by sulforhodamine B assay. Interleukin (IL)-1β, caspase-1, microtubule-associated protein-1 light chain 3-II/I and p62 were determined by western blotting and ELISA. The phosphorylation (p-) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Although autophagy and pyroptosis are two independent patterns of cell death, Jiang et al proved that there is an important feedback network between autophagy, NF-κB signaling pathway and LPS-induced pyroptosis [ 12 ]. Cardiovascular drugs that have been widely used in clinical practice, such as Carvedilol, an α-, β-blocker, are being tested to attenuate macrophage pyroptosis via autophagy activation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy and pyroptosis are two independent patterns of cell death, Jiang et al proved that there is an important feedback network between autophagy, NF-κB signaling pathway and LPS-induced pyroptosis [ 12 ]. Cardiovascular drugs that have been widely used in clinical practice, such as Carvedilol, an α-, β-blocker, are being tested to attenuate macrophage pyroptosis via autophagy activation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that RAPA can reduce the pyroptosis in various cell models [ 18 20 ] and inhibition of pyroptosis prolong the survival of a sepsis animal model [ 4 , 9 11 ]. In the present study, we found that RAPA inhibited pyroptosis and reduced the septic response in both LPS-induced HUVECs and PMA+LPS-activated human THP-1 cell models of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…ROS blockade with subsequently suppressed inflammasome activity by autophagy is one of the important mechanisms to antagonize pyroptosis. An important feedback network exists between autophagy, NF-κB signaling pathway, and pyroptosis ( Gao Y. et al, 2020 ). Wang et al reported that enhanced autophagy prevented pyroptotic cell death by eliminating excess ROS and negatively mediating the nuclear translocation of NF-κB P65 and NLRP3 inflammasome activation ( Wang X. et al, 2019 ).…”
Section: Possible Association Between Autophagy and Pyroptosis In Atherosclerosismentioning
confidence: 99%